2015
DOI: 10.17761/1531-2054-25.1.79
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness-Based Movement on Parameters of Stress

Abstract: The Mindfulness-Based Stress Reduction program (MBSR) of Kabat-Zinn includes a combination of sitting meditation, yoga, and walking; thus, movement is not emphasized primarily to induce a state of awareness. The purpose of this study was to investigate the effects of a Mindfulness-Based Movement Program (MBM) in women on parameters of stress and coping; that is, in contrast to MBSR, MBM primarily emphasized yoga to cultivate awareness. This study investigated: (a) an objective measure of stress (the cortisol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The abovementioned meditations have been widely studied from the molecular point of view. They influence the levels of several metabolites and biomarkers like hormones and neurotransmitters, as well as immune and neuroendocrine factors affected by stress and relevant to disease development and progression (Daube and Jakobsche, 2015;Robert-McComb et al, 2015;Twal et al, 2016;Househam et al, 2017). For example, TM, SK, and Zen meditation were shown to influence levels of cortisol, serotonin, melatonin, epinephrine and norepinephrine, gamma amino butyric acid (GABA), glutamate, and dehydroepiandrosterone (DHEA; reviewed in Kasala et al, 2014).…”
Section: Effects Of Sitting Meditationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abovementioned meditations have been widely studied from the molecular point of view. They influence the levels of several metabolites and biomarkers like hormones and neurotransmitters, as well as immune and neuroendocrine factors affected by stress and relevant to disease development and progression (Daube and Jakobsche, 2015;Robert-McComb et al, 2015;Twal et al, 2016;Househam et al, 2017). For example, TM, SK, and Zen meditation were shown to influence levels of cortisol, serotonin, melatonin, epinephrine and norepinephrine, gamma amino butyric acid (GABA), glutamate, and dehydroepiandrosterone (DHEA; reviewed in Kasala et al, 2014).…”
Section: Effects Of Sitting Meditationsmentioning
confidence: 99%
“…This latter is an 8-week integrated approach, an amalgam of mindfulness meditation, concentrative meditation, breathing exercises, Yoga, autogenic training, and Buddhist philosophy. In recent years many such protocols, combining different techniques to be applied for defined periods of time to various clinical settings, have been developed under various acronyms, such as Mindful Awareness Practices (MAP; Bower et al, 2014 ), Mindfulness-Based Movement (MBM; Robert-McComb et al, 2015 ) and more generally standardized as Mindfulness-Based Interventions (MBI; Black and Slavich, 2016 ). All protocols have become the subject of psychological, physiological, and molecular investigations ( Black and Slavich, 2016 ).…”
Section: Epigenetics Stress and The Importance Of Mindful Activitiementioning
confidence: 99%
“…Similarly, an experiential learning activity based around gender inequity in the workplace reduced feelings of reactance and promoted self‐efficacy (Zawadzki, Danube, & Shields, ). Other activities have demonstrated that experiential activities go beyond personal insight and provide the basis for altering personal behavior to include reducing aggressive behavior (Teglasi & Rothman, ), reducing stress (Robert‐McComb et al., ), and decreasing chronic combat‐related posttraumatic stress disorder conditions (Gelkopf, et al., ; Wolf & Mehl, ).…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…Yogic techniques have been found effective in management of anxiety. [ 5 ] Rajyoga meditation is believed to harmonizes spiritual, mental and physical energy, thereby increasing inner strength to lead a stress-free life.…”
Section: Introductionmentioning
confidence: 99%